Voices in the theater - Santos, A.S (SPRG Trilogy, 2015)
Voices in the theater is the first installment of A. S. Santos's three-book Young Adult Paranormal Romance. Follow Sam and her friends in the Student Paranormal Research Group as they encounter bizarre and often dangerous supernatural occurrences, battle demons both spiritual and psychological, and navigate adolescence and young love.